A New Era? Timor-Leste after the UN - Ingram, Sue; Kent, Lia; McWilliam, Andrew (ANU Press, 2015)
Timor-Leste has made impressive progress since its historic achievement of independence in 2002. From the instability that blighted its early years, the fledgling democratic country has achieved strong economic growth and a gradual reinstatement of essential social services. A decade on in 2012, Presidential and Parliamentary elections produced smooth political transitions and the extended UN peacekeeping presence in the country came to an end. But significant challenges remain. This book, a product of the inaugural Timor-Leste Update held at The Australian National University in 2013 to mark the end of Timor-Leste's first decade as a new nation, brings together a vibrant collection of papers from leading and emerging scholars and policy analysts. Collectively, the chapters provide a set of critical reflections on recent political, economic and social developments in Timor-Leste. The volume also looks to the future, highlighting a range of transitions, prospects and undoubted challenges facing the nation over the next 5-10 years. Key themes that inform the collection include nation-building in the shadow of history, trends in economic development, stability and social cohesion, and citizenship, democracy and social inclusion. The book is an indispensable guide to contemporary Timor-Leste.